2014
DOI: 10.1002/anie.201405195
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine‐Free Pyrotechnics: Copper(I) Iodide as a “Green” Blue‐Light Emitter

Abstract: The generation of blue-light-emitting pyrotechnic formulations without the use of chlorine-containing compounds is reported. Suitable blue-light emission has been achieved through the generation of molecular emitting copper(I) iodide. The most optimal copper(I) iodide based blue-light-emitting formulation was found to have performances exceeding those of chlorine-containing compositions, and was found to be insensitive to various ignition stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 6 publications
0
24
0
2
Order By: Relevance
“…The first example of an effective chlorine-free blue-lightemitter is summarized in Table 18 [40]. It was found that copper(I) iodide (CuI) could also serve as an effective bluelight-emitter under cool-burning conditions, which was achieved by the use of guanidinium nitrate (Table 19).…”
Section: Removal Of Heavy Metals From Pyrotechnic Illuminantsmentioning
confidence: 99%
“…The first example of an effective chlorine-free blue-lightemitter is summarized in Table 18 [40]. It was found that copper(I) iodide (CuI) could also serve as an effective bluelight-emitter under cool-burning conditions, which was achieved by the use of guanidinium nitrate (Table 19).…”
Section: Removal Of Heavy Metals From Pyrotechnic Illuminantsmentioning
confidence: 99%
“…Furthermore, copper flames are known to be of low intensity. [12] It was estimated that the radiant flux of copperf lamesw as five times lower than that of barium and ten times lower than that of strontium, with regard to dominating band emissionsi nt he UV/Vis region. Therefore, any impurities can have as ignificant influence on blue color flame production.…”
Section: Butane Flame Testsmentioning
confidence: 99%
“…[1,12] Some researchers describe that the CuOH emission is due to C-type chemiluminescence, [1] which results from non-thermal excitation.T his might explainw hy CuOH does not produce al inear spectrum, but only one large diffuse band in the green region (l = 535-555nm). When CuCl and CuBr salts were introduced deeper in the flame envelope, av ivid blue emission (Cu halide)w ith ag reen outer envelope (CuOH) was observed.…”
Section: Butane Flame Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this approach produced acceptable results, [7] the use of new ingredients in energetic materials requires extensive testing,a so utlined in NATO STANAG 4147, and may lead to the ultimate rejection of new ingredients. [8] Although chlorine-free variants of green-and blue-lightemitting pyrotechnic compositions have been reported, [9,10] the development of achlorine-free red-light-emitting flare of both high luminosity and deep saturation has remained elusive.…”
mentioning
confidence: 99%